Determination of intrinsic mobility of a bilayer oxide thin-film transistor by pulsed I–V method. (30th March 2017) - Woo, Hyunsuk; Kim, Taeho; Hur, Jihyun; Jeon, Sanghun
Abstract: Amorphous oxide semiconductor thin-film transistors (TFT) have been considered as outstanding switch devices owing to their high mobility. However, because of their amorphous channel material with a certain level of density of states, a fast transient charging effect in an oxide TFT occurs, leading to an underestimation of the mobility value. In this paper, the effects of the fast charging of high-performance bilayer oxide semiconductor TFTs on mobility are examined in order to determine an accurate mobility extraction method. In addition, an approach based on a pulse I D –V G measurement method is proposed to determine the intrinsic mobility value. Even with the short pulse I D –V G measurement, a certain level of fast transient charge trapping cannot be avoided as long as the charge-trap start time is shorter than the pulse rising time. Using a pulse-amplitude-dependent threshold voltage characterization method, we estimated a correction factor for the apparent mobility, thus allowing us to determine the intrinsic mobility.